PENGARUH CORPORATE GOVERNANCE DAN INTENSITAS PERSEDIAAN TERHADAP MANAJEMEN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015 - Lia Warokha, 13.05.52.0079; Poerwati, Rr. Tjahjaning (Students' Journal of Accounting and Banking, 2017)
The study examines the influence of Corporate Governance, inventory intensity and auditor reputasion to tax management. Tax management is measured by effective tax rate. Corporate governance are measured by number of commissioner and percentage of independent commissioner. This research sample is manufactured company for years 2013-2015 selected by using method of purposive sampling. There are 254 companies fulfilling criterions. This research used multiple regression analysis. The results of this research indicates that the number of commissioner and the proportion of independent commissioners tax management significantly. Meanwhile, inventory intensity and auditor reputasion does not significantly influence the company's tax management.Keywords: Number of Commissioner, Percentage of Independent Commissioner, Inventory Intensity, Auditor Reputasion, Tax Management